The effect of topical airway anesthesia on hemodynamic profiles during the induction period in patients undergoing cardiac surgery: Study protocol for a randomized controlled trial - Du, Wenya; Lv, Meng; Chen, Tingting; Sun, Xiaxuan; Wang, Jihua; Zhang, Haixia; Wei, Chuansong; Liu, Yi; Qiao, Changlong; Wang, Yuelan (Frontiers in Cardiovascular Medicine, 2022)
Background：Patients scheduled for cardiac surgery are often accompanied by cardiac dysfunction and hemodynamic instability. However, conventional anesthesia induction strategy using high-dose intravenous anesthetics is often associated with persistent and recurrent hypotension after tracheal intubation. The aim of this study is to investigate the effect of topical airway anesthesia on hemodynamic profile of patients undergoing cardiac surgery during the induction period. Methods：This is a superiority, single-blind, randomized controlled study with two parallel groups. Participants scheduled to undergo elective cardiac surgery will be screened into two blocks according to New York Heart Association (NYHA) grade and then randomly allocated to two groups within the block in the ratio of 1:1, the conventional induction group and the combined topical airway anesthesia induction group. The combined topical airway anesthesia induction strategy includes aerosol inhalation airway anesthesia, subglottic airway anesthesia and general anesthesia induction using low-dose intravenous anesthetics. The primary outcome is the area under the curve (AUC) of blood pressure below baseline mean arterial pressure from 3 minutes to 15 minutes after endotracheal intubation. Secondary outcomes include AUC above baseline mean arterial pressure and below baseline mean arterial pressure at other time points, the highest and lowest values of arterial blood pressure during the induction period, type and dose of vasoactive drugs, incidence of arrhythmias, cardiac function, and incidence of postoperative hoarseness and sore throat. Discussion: The study will explore whether aerosol inhalation airway anesthesia and subglottic airway anesthesia would reduce the incidence and duration of hypotension during the induction period in patients undergoing cardiac surgery. Trial Registration: The Research Ethics Committee of The First Affiliated Hospital of Shandong First Medical University has approved this study (YXLL-KY-2021(080)). This trial was registered at www.ClinicalTrials.gov (NCT05323786). Dissemination：The results of this study will be disseminated in international peer-reviewed journals.